2017
DOI: 10.1111/mec.14192
|View full text |Cite
|
Sign up to set email alerts
|

Ambient temperature‐mediated changes in hepatic gene expression of a mammalian herbivore (Neotoma lepida)

Abstract: Herbivores regularly ingest natural toxins produced by plants as a defence against herbivory. Recent work suggests that compound toxicity is exacerbated at higher ambient temperatures. This phenomenon, known as temperature-dependent toxicity (TDT), is the likely result of decreased liver function at warmer temperatures; however, the underlying cause of TDT remains speculative. In the present study, we compared the effects of temperature and dietary plant toxins on differential gene expression in the liver of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…While we lack specific information about particulars of liver enzymes and gene expression for mice in the present study, we speculate that this result may reflect a difference in hepatic gene expression driven by ambient temperature. Connors et al () found a similar interaction between ambient temperature and PSM ingestion on gene expression in woodrats. They found that differential gene expression in the liver was greater at a cooler temperature compared to a warmer temperature on a control diet, and that even though the warm temperature was within the thermal neutral zone, gene expression at this temperature indicated a stressed state.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…While we lack specific information about particulars of liver enzymes and gene expression for mice in the present study, we speculate that this result may reflect a difference in hepatic gene expression driven by ambient temperature. Connors et al () found a similar interaction between ambient temperature and PSM ingestion on gene expression in woodrats. They found that differential gene expression in the liver was greater at a cooler temperature compared to a warmer temperature on a control diet, and that even though the warm temperature was within the thermal neutral zone, gene expression at this temperature indicated a stressed state.…”
Section: Discussionmentioning
confidence: 75%
“…Captive feeding experiments revealed that woodrats chose to eat significantly less terpene‐rich juniper extract at a warmer temperature (Dearing, Forbey, McLister, & Santos, ) and that a warm temperature reduced the tolerance of woodrats to the toxins in creosote (Kurnath, Merz, & Dearing, ). Further studies have shown that the effects of temperature on PSM toxicity may be related to liver function, with warmer temperatures resulting in reduced hepatic gene expression and slower clearance rates of hypnotic agents (Connors, Malenke, & Dearing, ; Kurnath & Dearing, ). The liver is known to play a major role in the acclimation of animals to a toxin‐rich diet.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations